2012
DOI: 10.1080/02646838.2011.649473
|View full text |Cite
|
Sign up to set email alerts
|

Japan–France–US comparison of infant weaning from mother’s viewpoint

Abstract: Background: Breastfeeding and weaning are strongly connected with infant–mother mutual autonomy, and hence are good touchstones to examine the characteristics of the mother–child relationship. Comparison of the weaning practice gives a framework to understand characteristics of the mother–infant relationship. Objective: The purpose of this study was to compare three industrialised countries concerning the relationship between feeding and weaning practices and its reasons, mother's perception of child care, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 28 publications
2
25
0
Order By: Relevance
“…The time for initiation of complementary foods varies slightly in the various guidelines, but approximately 4–6 months is recommended . The recommended time differs according to country, culture, tradition, and individual preference . WHO and UNICEF reported that the global rate of exclusive breast‐feeding for infants <6 months of age was 40% .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The time for initiation of complementary foods varies slightly in the various guidelines, but approximately 4–6 months is recommended . The recommended time differs according to country, culture, tradition, and individual preference . WHO and UNICEF reported that the global rate of exclusive breast‐feeding for infants <6 months of age was 40% .…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20] The recommended time differs according to country, culture, tradition, and individual preference. [20][21][22][23] WHO and UNICEF reported that the global rate of exclusive breast-feeding for infants <6 months of age was 40%. 24 In Japan, the rate of exclusive breast-feeding has 25 These findings are consistent with those reported for other cohorts in Japan.…”
Section: Breast-feeding Prevalencementioning
confidence: 99%
“…Lacking of breast stimulation will cause a by seeking of babies will cause a decrease in breastfeeding production. 26 Then, it is also strengthened by breastfeeding deficiency which becomes the reasons for mothers to give supplemental food. There were several complementary reasons that were done by another study such as food for infants were better than mother's own breastfeeding, inconvenience to give breastfeeding in all time, and other people influence, 27 simple and free on young mothers.…”
Section: Mother's Behavior and Exclusive Breastfeeding (Ebf) Practicementioning
confidence: 99%
“…17 Perceptions and practice of weaning by mothers is dependant on multiple factors and varies from culture to culture and region to region. 32 Quantity, quality and frequency of weaning foods are the main areas which are usually explored in one or another way. 33 It was found that the mothers of 'awared and active group' (AA group) were more awared and knowledgeable than the 'ignorant and docile group' (ID group).…”
Section: Discussionmentioning
confidence: 99%